Semivolatility managed portfolios - Silva, Daniel Batista da (2021)
Volatility management is still a relevant topic of discussion in the literature, with works arguing both for its efficiency or inefficacy. We study a new framework building on top of this kind of strategy and attempting to solve common critiques on the way they are analysed. By decomposing volatility into its upside and downside components, our constructions allow for better control of both types of risk as they are perceived for the common investor. Leveraging in times of “good” volatility and deleveraging in times of “bad” volatility seems to perform generally better than unmanaged portfolios or even the traditional volatility management. The results point to semivolatility managed portfolios being a fair strategy in active portfolio management, both in a mean-variance or mean-semivariance framework.